Studi Geomorfologi Daerah Kedungpoh dan Sekitarnya, Kabupaten Gunung Kidul, Daerah Istimewa Yogyakarta - Suci Febria Lestari; Harnani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The Kedungpoh area and its surroundings in Gunung Kidul Regency, Yogyakarta, are part of the Wonosari Basin, which exhibits complex geomorphological characteristics resulting from the interaction of lithology, geological structures, and exogenic processes. This study aims to identify landform units and analyze the geomorphic processes that contribute to the development of geomorphology in the study area. The methods employed include morphological, morphometric, and morphogenetic analyses through the interpretation of topographic maps, DEM data, and direct field observations. The results indicate that the analyzed area can be classified into seven main geomorphic units: Low Denudational Hills with Moderate Erosion, Denudational Hills with High Erosion, High Denudational Hills with High Erosion, Fault Zone Hills with High Erosion, Floodplain, Irregular Meandering Channel, and Lapilli Plain. The morphology of the study area is controlled by variations in Tertiary lithology, the development of major fault structures such as the Pilangrejo Fault and the Pengkol Fault, as well as intensive fluvial and denudational processes. The dominant geomorphic processes include denudation, fluvial activity, and volcanic deposition, with erosion intensity ranging from moderate to high. These findings provide insight into the dynamics of landform development in the Kedungpoh area, which are controlled by the interaction of geological structures, lithology, and ongoing geomorphic processes.